Time and performer training - Evans, Mark 1957-; Thomaidis, Konstantinos; Worth, Libby 1955- (London New York Routledge/Taylor & Francis Group, 2019)
"Time and Performer Training addresses the importance and centrality of time and temporality to the practices, processes, and conceptual thinking of performer training. Notions of time are embedded in almost every aspect of performer training, and so contributors to this book look at: - age/aging and children in the training context - how training impacts over a lifetime - the duration of training and the impact of training regimes over time - concepts of timing and the 'right' time - how time is viewed from a range of international training perspectives - collectives, ensembles and fashions in training, their decay, or endurance. Through focusing on time and the temporal in performer training, this book offers innovative ways of integrating research into studio practices. It also steps out beyond the more traditional places of training to open up time in relation to contested training practices that take place online, in festival spaces, and in folk or amateur practices. Ideal for both instructors and students, each section of this well-illustrated book follows a thematic structure and includes full-length chapters alongside shorter provocations. Featuring contributions from an international range of authors who draw on their backgrounds as artists, scholars, and teachers, Time and Performer Training is a major step in our understanding of how time affects the preparation for performance"-- Provided by publisher.
Foreword: embodied time / Anne Bogart -- Introduction: expansive temporalities of performer training / Konstantinos Thomaidis, with Mark Evans and Libby Worth -- Lecoq: training, time and temporality / Mark Evans -- A long view of theatre training / David Wiles -- Time in noh theatre performance and training: conversations with Udaka Tatsushige / Diego Pellecchia -- A materialist feminist perspective on time in actor training: the commodity of illusion / Evi Stamatiou -- The ecology of a sense of good timing / Darren Tunstall -- Gathering ghosts: Lecoq's twenty movements as a technique to mark time / Jenny Swingler -- Adavu: drilling through time / Mark Hamilton -- RSVP and the timely experience / Gillian Raby -- Formative trainings in Carnatic vocal music: a three-way conversation through time / Tim Jones -- Change, continuity and repetition: married to the Balinese mask / Tiffany Strawson -- The feeling of time / Jennifer Jackson -- The dance of opposition: repetition, legacy and difference in third theatre training / Jane Turner and Patrick Campbell -- Out of time: beyond presence and the present -- Bridging monuments: on repetition, time and articulated knowledge at the Bridge of Winds Group / Adriana La Selva -- The always-not-yet / always-already of voice perception: training towards vocal presence / Konstantinos Thomaidis -- Rehearsing (inter)disciplinarity: training, production practice, and the 10,000-hour problem / Laura Vorwerg -- Beyond the "time capsule": recreating Korean narrative temporalities in pansori singing / Chan E. Park -- Simultaneity and asynchronicity in performer training: a case study of massive open online courses as training tools / Jonathan Pitches -- Festival time / Kate Craddock -- Time, friendship and "collective intimacy": the point of view of a co-devisor from within Little Bulb Theatre / Eugénie Pastor -- Time moves: temporal experiences in current London-based training for traditional clog and rapper sword dances / Libby Worth.
Includes bibliographical references and index.
Keywords: Act; Actors -- Training; Space and time in the theatre